Risk of Gastrointestinal Adverse Events in Cancer Patients Treated With Immune Checkpoint Inhibitor Plus Chemotherapy: A Systematic Review and Meta-Analysis - Yang, Wenhan; Men, Peng; Xue, Huimin; Jiang, Mingyan; Luo, Qiuhua (Frontiers in Oncology, 2020)
Background: The combination of immune checkpoint inhibitors (ICIs) and chemotherapy can improve clinical outcomes in the treatment of various tumors, but may also be associated with more adverse events (AEs). We performed a systematic review and meta-analysis to characterize the risk of gastrointestinal AEs in cancer patients treated with ICI plus chemotherapy. Methods: This review was based on comprehensive search through PubMed, EMBASE, and the Cochrane Library for randomized controlled trials (RCTs) that reported gastrointestinal AEs following the use of ICI plus chemotherapy. Literature screening, data extraction, and quality evaluation were performed by two individual reviewers. Revman (version 5.3) was used for meta-analysis. Risk ratios (RR) with 95% confidence interval (CI) were calculated. Meta-analysis was conducted according to different types of ICIs [programmed death 1 (PD-1), programmed death ligand 1 (PD-L1), and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) inhibitors]. Results: After a full-text review, 10 trials involving 5,142 patients were included in the study. Compared with chemotherapy alone, PD-1 inhibitor plus chemotherapy significantly increased the risk of diarrhea (RR = 1.38, 95% CI, 1.13–1.68, P = 0.001; I2 = 0%) and colitis (RR = 2.90, 95% CI, 1.02–8.21, P = 0.050; I2 = 0%), PD-L1 inhibitor plus chemotherapy significantly increased the risk of nausea (RR = 1.17, 95% CI, 1.02-1.35, P = 0.020; I2 = 0%), while CTLA-4 inhibitor plus chemotherapy significantly increased the risk of decreased appetite (RR = 1.49, 95% CI, 1.17–1.90, P = 0.001; I2 = 0%), diarrhea (RR = 2.23, 95% CI, 1.90–2.63, P < 0.00001; I2 = 0%), and colitis (RR = 28.39, 95% CI, 5.59–144.24, P < 0.001; I2 = 0%). Conclusions: This meta-analysis demonstrated that ICI plus chemotherapy is associated with a higher risk of gastrointestinal AEs. However, combining different ICIs may lead to diverse gastrointestinal toxicities. Clinicians should be aware of these AEs in the application of ICI plus chemotherapy.